Gonia picea - DRABER-MOŃKO, Agnieszka (Zenodo, 2015)
Gonia picea (Robineau-Desvoidy, 1830) * Spallanzania picea Robineau-Desvoidy, 1830: 78. Type localities: France and Spain. Material examined: North Korea, Phjǒngjang Prov., Moran-yong, 27. 08. 1970, 1 male, leg. R. Bielawski and M. Mroczkowski. Distribution: Palaearctic: Europe: Spain, France, Hungary, Poland, Germany, Great Britain, Sweden, Russia (European part), Transcaucasia, Israel (Herting & Dely-Draskovits 1993, Draber-Mońko 2007), Turkmenia, Russia (S. Siberia (Irkutsk), N. Far East: Kamchatka) (Richter 2004), Japan (Hokkaido, Honshu, Shikoku, Kyushu) (Shima 2014). China Provinces (Anhui, Beijing M., Hebei, Henan, Heilongjiang, Jilin, Jiangsu, Liaoning, Inner Mongolia, Qinghai, Sichuan, Shandong, Shanghai M., Shaanxi, Shanxi, Tianjin M., Xinjiang Uygur A. R., Tibet); Oriental: Taiwan, China Provinces (Fujian, Guizhou, Hunan, Jiangxi, Yunnan, Zhejiang) (O’Hara, Shima & Zhang 2009). First record from Korea. : Published as part of DRABER-MOŃKO, Agnieszka, 2015, State of knowledge of the tachinid fauna of Eastern Asia, with new data from North Korea. Part V. Exoristinae, pp. 79-98 in Fragmenta Faunistica 58 (2) on page 93, DOI: 10.3161/00159301FF2015.58.2.079, http://zenodo.org/record/6251824 : {"references": ["Richter V. A. 2004. Fam. Tachinidae - tachinids. In: Sidorenko V. S. (ed.), Key to the insects of Russian Far East. Vol. VI. Diptera and Siphonaptera. Part 3 pp. 148 - 398. Vladivostk, Dal'nauka. 657 pp. [In Russian].", "SHIMA H. 2014. Family Tachinidae. In: NAKAMURA, T., SAIGUSA, T. & SUWA, M. (eds.), Catalogue of the insects of Japan. Volume 8. Diptera. Part 2. Brachycera Schizophora, pp: 832 - 882. Entomological Society of Japan, Fukuoka, XIV + 562 pp.", "O'HARA J. E., SHIMA H. & ZHANG C. T. 2009. Annotated Catalogue of the Tachinidae (Insecta: Diptera) of China. Zootaxa 2190: 1 - 236."]}